2022
DOI: 10.1371/journal.pcbi.1010442
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding costly mistakes in groups: The evolution of error management in collective decision making

Abstract: Individuals continuously have to balance the error costs of alternative decisions. A wealth of research has studied how single individuals navigate this, showing that individuals develop response biases to avoid the more costly error. We, however, know little about the dynamics in groups facing asymmetrical error costs and when social influence amplifies either safe or risky behavior. Here, we investigate this by modeling the decision process and information flow with a drift–diffusion model extended to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…by a frequency-based or model-based strategy; [ 168 ]). In addition, individuals can use diverse state-based strategies [ 40 ], including confidence in own judgements [ 169 ] and amount of personal information [ 170 ] to decide whether to use social information in the first place.…”
Section: Building Blocks Of Collective Adaptationmentioning
confidence: 99%
See 3 more Smart Citations
“…by a frequency-based or model-based strategy; [ 168 ]). In addition, individuals can use diverse state-based strategies [ 40 ], including confidence in own judgements [ 169 ] and amount of personal information [ 170 ] to decide whether to use social information in the first place.…”
Section: Building Blocks Of Collective Adaptationmentioning
confidence: 99%
“…One example is Tump et al . 's [ 170 ] combination of drift-diffusion cognitive models of individual and social learning with an evolutionary process that selects parameters of drift-diffusion models that are best adapted to particular group structures and problems with different costs of errors. Another example is Cooney et al .…”
Section: Studying Collective Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, experimental research on individual police officers in shooting simulators has shown that the decision to shoot is typically made faster than the decision not to shoot, explained by a bias in the start point (Pleskac et al, 2018). Such asymmetries in decision timing-which appear in various social contexts (Tump, Pleskac, et al, 2022)-are predicted to have consequences on which decisions (and potential biases) are amplified in a social context, because early-arriving social information typically exerts a stronger influence on the collective (Tump, Pleskac, et al, 2022;Tump, Wolf, et al, 2022). The prediction at the collective level is thus that having multiple police officers in a shooting simulator will increase the likelihood to shoot.…”
Section: The Emergence Of Biases In Collective Systemsmentioning
confidence: 99%